TICKS (ACRINA) FROM DOMESTIC ANIMALS IN CENTRAL IRAQ - Al-Azawi , B.; Al-Obeidy, T. (The Iraqi Journal of Veterinary Medicine, 1992)
A survey was done to study the ticks of domestic animals in Baghdad and some neighboring areas in 1987. Two genera with 3 species and two new subspecies of ticks were identified. Hyalomma marginatum turanica pomerantsev was the most abundant among the population of the domestic animals than the other two species Hyalomma anatolicum excavatum Koch and Rhipicephalus turanicus Pomeratsev and Matikashvili. Older age and colored animals were more infested with ticks than the young and lightly colored. Ticks were mostly found attaching firmly to skin of ears and udder in females and near the scrotum in males.